PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS BERDASARKAN RESILIENSI MATEMATIS SISWA MTS MUHAMMADIYAH 02 PEKANBARU - Ramadani, Ramadani; Muhandaz, Ramon (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The ability to think creatively is needed by students in mathematics learning activities, because creativity raises ideas in solving mathematical problems, so that the expected learning objectives are achieved. In addition, the mathematical resilience factor is needed to make students more persistent, never give up, enjoy being challenged, so that students' perspective on mathematics is not something to be afraid of anymore. This study aims to determine the effect of an open-ended approach on the mathematical creative thinking ability based on the mathematical resilience of Madrasah Tsanawiyah (MTs). This type of research is an experimental design that uses a factorial design. The selected population has been subjected to a one-way ANOVA test with the results having an average similarity, so that the sample was taken using the Cluster Random technique with randomly selected samples, namely class VIII-1 which was selected as the experimental class and class VIII-2 was selected as the control class. The results showed: 1) there were differences in mathematical creative thinking skills between students learning with open-ended learning and students learning using conventional learning; 2) there are differences in mathematical creative thinking abilities between students who have high, medium and low mathematical resilience; 3) while for interaction there is no interaction between the open-ended learning approach and students' mathematical resilience to mathematical creative thinking abilities. So the results of this study can be used to improve mathematics learning in class.